1997
DOI: 10.1242/jcs.110.11.1279
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of embryonic stem cells into adipocytes in vitro

Abstract: Embryonic stem cells, derived from the inner cell mass of murine blastocysts, can be maintained in a totipotent state in vitro. In appropriate conditions embryonic stem cells have been shown to differentiate in vitro into various derivatives of all three primary germ layers. We describe in this paper conditions to induce differentiation of embryonic stem cells reliably and at high efficiency into adipocytes. A prerequisite is to treat early developing embryonic stem cell-derived embryoid bodies with retinoic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 370 publications
(8 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…As in vitro systems, various pre-adipose cell lines and primary cultures of adipose-derived stromal vascular cells have been successfully employed for adipogenic differentiation studies (Kanazawa et al 2005;Choi et al 2007). In addition to these models, embryonic stem cells have been demonstrated to differentiate into mature adipocytes in vitro (Dani et al 1997;Li et al 2007). In this study, we demonstrated that hAMSCs are capable of differentiating into adipocyte, chondrocyte, osteocyte and neuronal-like cells; also, we demonstrated in vitro regulation of adipogenesis, using a hAMSC model.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…As in vitro systems, various pre-adipose cell lines and primary cultures of adipose-derived stromal vascular cells have been successfully employed for adipogenic differentiation studies (Kanazawa et al 2005;Choi et al 2007). In addition to these models, embryonic stem cells have been demonstrated to differentiate into mature adipocytes in vitro (Dani et al 1997;Li et al 2007). In this study, we demonstrated that hAMSCs are capable of differentiating into adipocyte, chondrocyte, osteocyte and neuronal-like cells; also, we demonstrated in vitro regulation of adipogenesis, using a hAMSC model.…”
Section: Discussionmentioning
confidence: 56%
“…2007). In addition to these models, embryonic stem cells have been demonstrated to differentiate into mature adipocytes in vitro (Dani et al . 1997; Li et al .…”
Section: Discussionmentioning
confidence: 99%
“…KLF2 -/-ES cells were created using a two-step targeting procedure as described previously (14). The established protocol for EB culture and differentiation into adipocytes is described previously (23). In summary, KLF2 -/and KLF2 +/+ ES cells were grown in DMEM supplemented with 15% fetal calf serum on mitomycin-treated fibroblast cell layers.…”
Section: T3l1 Preadipocytementioning
confidence: 99%
“… 44 , 45 EBs derived from human or murine ESCs have been used to study cell fate decisions and the differentiation of various cell types during embryogenesis as a good model for hematopoietic development. 46 , 47 …”
Section: Hematopoietic Development In a Dishmentioning
confidence: 99%